Peripartum Primary Prophylaxis Inferior Vena Cava Filter Placement in a Patient with Stage IV B-Cell Lymphoma Presenting with a Pathologic Femur Fracture - David M. Sherer; Mudar Dalloul; Henry James Behar; Ghadir Salame; Roy Holland; Harry Zinn; Ovadia Abulafia (Thieme Medical Publishers, Inc., 2015)
Abstract Background Pulmonary embolus (PE) remains a leading etiology of maternal mortality in the developed world. Increasing utilization of retrievable inferior vena cava (IVC) filter placement currently includes pregnant patients. Case A 22-year-old woman at 27 weeks' gestation was diagnosed with Stage IV high-grade malignant B cell lymphoma following pathologic femur fracture. Significant risk factors for PE led to placement of primary prophylaxis IVC filter before cesarean delivery, open reduction and internal fixation of the fractured femur, and chemotherapy. Conclusion This case supports that primary prophylaxis placement of IVC filters in highly selected pregnant patients may assist in decreasing PE-associated maternal mortality.